Atividades séricas da aspartato aminotransferase, creatina quinase e lactato desidrogenase de eqüinos submetidos ao teste padrão de exercício progressive em esteira - Thomassian, Armen [UNESP]; de Carvalho, Fernanda [UNESP]; Watanabe, Marcos Jun [UNESP]; da Silveira, Veridiana Fernandes [UNESP]; Alves, Ana Liz Garcia [UNESP]; Hussni, Carlos Alberto [UNESP]; Nicoletti, José Luiz de Mello [UNESP] (My University, 2007)
The aim of this study was to determine the serum activities of enzymes aspartate aminotransferase, creatine kinase and lactate dehydrogenase in Arabian horses submitted to exercise on high-speed equine treadmill. Eleven mature Arabian horse were training and submitted to Standard Incremental Exercise Test on high-speed equine treadmill. Venous blood samples were taken before exercise, immediately and 30 min, 60min, 3h, 6h, 24h, 3 days and 5 days after exercise. The serum activity aspartate aminotransferase, creatine kinase and lactate dehydrogenase were determined. The serum activies of AST, CK and LDH increase immediately and returned to baseline value 30 minutes after exercise. The AST enzyme activity increased at 12 hours and 24 hours, CK at 3 hours and 6 hours, and LDH at 24 hours after Standard Incremental Exercise Test.
Serum activities of aspartate aminotransferase, creatine kinase and lactate dehydrogenase in arabian horses submitted to standard incremental exercise test
Keywords: AST; CK; Equine; Exercise; LDH; Treadmill; Equidae